Assessment of tacrolimus intrapatient variability in stable adherent transplant recipients: Establishing baseline values. Issue 5 (26th December 2018) - Leino, Abbie D.; King, Eileen C.; Jiang, Wenlei; Vinks, Alexander A.; Klawitter, Jost; Christians, Uwe; Woodle, E. Steve; Alloway, Rita R.; Rohan, Jennifer M.
Abstract : The purpose of this study was to determine the intrapatient (within the same patient) variability of tacrolimus in adherent patients. Daily tacrolimus trough levels were obtained at home using dried blood spot technology in kidney and liver transplant recipients. Patients were randomized to receive 3 formulations of tacrolimus, each for two 1‐week periods. Adherence was monitored by patient diary, pill counts, and use of the Medication Event Monitoring System (MEMS). Variability was quantified as the coefficient of variation (CV). Comparison of CV between groups was by independent t test or one‐way ANOVA as appropriate. The population was found to be adherent with a rate of 99.9% with a mean interval between the evening and morning dose of tacrolimus of 11.86 hours. The median CV for the entire population was 15.2% (range 4.8%‐110%). There were no differences in CV by allograft type or tacrolimus formulation. The multivariate analysis did not identify any demographic characteristics associated with a CV > 30%. In a highly adherent population, tacrolimus did not display high intrapatient variability. Given the association between IPV and poor allograft outcomes, future studies are needed to quantitate the influence of adherence and establish target IPV goals. Abstract : In a highly adherent and clinically stable population of kidney and liver transplant recipients, tacrolimus trough levels do not display high intrapatient variability when calculated from daily levels obtained at home using dried blood spot technology.